An unusual case of venous varix on forehead - Bali, Sharadendu; Pundeer, Sameer; Utaal, Maneshwar Singh (International Surgery Journal, 2018)
Vascular anomalies include a wide number of disorders from a simple birthmark to life threatening entities. One such vascular anomaly is venous varix which is a commonly encountered case by a general surgeon although venous varix occurring on the forehead as being reported here is a rarity. Authors present a case of swelling over forehead at orbital verge which becomes prominent on performing valsalva maneuver. Case is of a 10year old girl brought to OPD with complaints of swelling over the left side of forehead since birth which becomes prominent on valsalva maneuver, with no associated complaints of pain or difficulty in eye opening. On examination, there was a 2cm diameter swelling present over the left forehead just above the medial margin of left eyebrow. CECT Brain showed no bony or intra orbital extension. Patient underwent excision of the varix. Postoperatively patient recovered well and discharged with cosmetic satisfaction.